2021
DOI: 10.1007/s00332-020-09673-2
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Based Reduced Modelling and Data-Based Estimation of Opinion Spreading

Abstract: We investigate opinion dynamics based on an agent-based model and are interested in predicting the evolution of the percentages of the entire agent population that share an opinion. Since these opinion percentages can be seen as an aggregated observation of the full system state, the individual opinions of each agent, we view this in the framework of the Mori–Zwanzig projection formalism. More specifically, we show how to estimate a nonlinear autoregressive model (NAR) with memory from data given by a time ser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, it is shown that the learning rate is then independent of the dimension, making their approach suitable for large-scale systems. The data-driven approach described in [25] utilizes memory terms to improve the accuracy of the coarse-grained model.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is shown that the learning rate is then independent of the dimension, making their approach suitable for large-scale systems. The data-driven approach described in [25] utilizes memory terms to improve the accuracy of the coarse-grained model.…”
Section: Introductionmentioning
confidence: 99%
“…For a time-discrete ABM with a clustered interaction network it has recently been shown that the state of the system for future time steps depends not only on the present time step, but also on the past. A data-driven method involving memory terms is proposed to mitigate this issue [48].…”
Section: Introductionmentioning
confidence: 99%